Development of a Fully Continuous‐Flow Approach Towards Asymmetric Total Synthesis of Tetrahydroprotoberberine Natural Alkaloids. Issue 33 (4th May 2022) - Li, Weijian; Jiang, Meifen; Liu, Minjie; Ling, Xu; Xia, Yingqi; Wan, Li; Chen, Fener
Abstract: Continuous flow synthetic technologies had been widely applied in the total synthesis in the past few decades. Fully continuous flow synthesis is still extremely focused on multi‐step synthesis of complex natural pharmaceutical molecules. Thus, the development of fully continuous flow total synthesis of natural products is in demand but challenging. Herein, we demonstrated the first fully continuous flow approach towards asymmetric total synthesis of natural tetrahydroprotoberberine alkaloids, (−)‐isocanadine, (−)‐tetrahydropseudocoptisine, (−)‐stylopine and (−)‐nandinine. This method features a concise linear sequence involving four chemical transformations and three on‐line work‐up processing in an integrated flow platform, without any intermediate purification. The overall yield and enantioselectivity of this four‐step continuous flow chemistry were up to 50 % and 92 % ee, respectively, in a total residence time of 32.5 min, corresponding to a throughput of 145 mg/h. Abstract : A fully continuous flow approach towards asymmetric total synthesis of four natural tetrahydroprotoberberine alkaloids, was developed through a concise linear sequence involving four chemical transformations and three on‐line work‐up processes without any intermediate purification. The overall yields and enantioselectivities obtained in this novel integrated flow platform were up to 50 % and 92 % ee, respectively, in a total residence time of 32.5 min.